Taxonomic review and distribution of giant water bugs (Hemiptera: Belostomatidae: Lethocerinae) in the Palearctic, Oriental, and Australian regions - Nattawut Sareein (2020)
© 2019 The Entomological Society of Korea and John Wiley & Sons Australia, Ltd The aim of the present study was to analyze the morphology and COI sequences of giant water bugs (Belostomatidae: Lethocerinae) that inhabit the Palearctic, Oriental, and Australian regions (i.e., three Lethocerus and a single Kirkaldyia species). Analysis revealed that both L. patruelis and L. indicus share two light stripes on the pronotum, but L. patruelis possesses narrower stripes and L. insulanus possesses an additional longitudinal narrow dark median band, whereas K. deyrolli was characterized by not having such markings. With regards to genetic analysis, the average intraspecific genetic distances of L. patruelis and L. indicus (from Palearctic and Oriental regions are 0.3 and 0.8%, respectively), but K. deyrolli which was collected from Northeast Asia, showed much higher intraspecific genetic distance (3.7%). The genetic distance between Kirkaldyia and Lethocerus (16.4–16.8%) is similar to that found between the genera of other hemipteran taxa. This study also newly reported the extended easternmost distribution of L. patruelis up to Surat Thani Province in southern Thailand. Along with K. deyrolli, which is considered threatened in South Korea and Japan, Lethocerus species have been facing threats in Southeast Asia, where they are heavily harvested and commonly sold in local markets as food. Therefore, future conservation efforts should be directed toward Lethocerus species in tropical Southeast Asia, especially the rarely found L. patruelis.